Recent advances in representation theory, quantum groups, algebraic geometry, and related topics: AMS special sessions on geometric and algebraic aspects of representation theory and quantum groups, and noncommutative algebraic geometry, October 13-14, 2012, Tulane University, New Orleans, Louisiana - Achar, Pramod N (Contemporary mathematics, 2014)
This volume contains the proceedings of two AMS Special Sessions `Geometric and Algebraic Aspects of Representation Theory' and `Quantum Groups and Noncommutative Algebraic Geometry' held October 13-14, 2012, at Tulane University, New Orleans, Louisiana, USA.Included in this volume are original research and some survey articles on various aspects of representations of algebras including Kac-Moody algebras, Lie superalgebras, quantum groups, toroidal algebras, Leibniz algebras and their connections with other areas of mathematics and mathematical physics.